Counterion-Mediated Assembly of Fluorocarbon–Hydrocarbon Surfactant Mixtures at the Air–Liquid Interface: A Molecular Dynamics Study - Xiaolong Quan; Tong Tong; Tao Li; Dawei Han; Baolong Cui; Jing Xiong; Zekai Cui; Hao Guo; Jinqing Jiao; Yuechang Wei (Molecules)
This study employs molecular dynamics simulations to investigate counterion effects (Li+, Na+, K+) on the interfacial aggregation of mixed short-chain fluorocarbon, Perfluorohexanoic acid (PFHXA), and Sodium dodecyl sulfate (SDS) surfactants. Motivated by the need for greener surfactant alternatives and a fundamental understanding of molecular interactions governing their behavior, we demonstrate that counterion hydration radius critically modulates system organization. K+ ions induce superior monolayer condensation and interfacial performance compared to Li+ and Na+ counterparts, as evidenced by threefold analysis: (1) RMSD/MSD-confirmed equilibrium attainment ensures data reliability; (2) 1D/2D density profiles and surface tension measurements reveal K+-enhanced packing density (lower solvent-accessible surface area versus Na+ and Li+ systems); (3) Electrostatic potential analysis identifies synergistic complementarity between SDS’s hydrophobic stabilization via dodecyl chain interactions and PFHXA’s charge uniformity, optimizing molecular-level charge screening. Radial distribution function analysis demonstrates K+’s stronger affinity for SDS head groups, with preferential sulfate coordination reducing surfactant-water hydration interactions. This behavior correlates with hydrogen-bond population reduction, attributed to SDS groups functioning as multidentate ligands—their tetrahedral oxygen arrangement facilitates cooperative hydrogen-bond networks, while counterion-specific charge screening competitively modulates bond formation. The resultant interfacial restructuring enables ordered molecular arrangements with lower system curvature than those observed in Li+ and Na+-containing systems. These findings elucidate counterion-mediated interfacial modulation mechanisms and establish K+ as an optimal candidate for enhancing PFHXA/SDS mixture performance through hydration-radius screening. The work provides molecular-level guidelines for designing eco-friendly surfactant systems with tailored interfacial properties.